Carrier Transport in a Deep Ultraviolet Mixed Quantum Well Light Emitting Diode - Friedhard Romer; Gregor Hofmann; Jakob Hopfner; Marcel Schilling; Anton Muhin; Tim Wernicke; Michael Kneissl; Bernd Witzigmann (IEEE Photonics Journal, 2024)
Aluminium Gallium Nitride (AlGaN) based light emitting diodes (LED) are the enabling technology for compact emitters of deep ultraviolet (DUV) radiation and are in high demand for environmental and medical applications. The efficiency of recent DUV LEDs is in the range of a few percent providing some potential for improvement. Apart from the light extraction efficiency the hole injection into the active region presents a major obstacle towards more efficient DUV LEDs. In this work, we investigate the emission spectra of a mixed multi quantum well (MQW) DUV LED to attain details on the active region carrier transport that allow an improvement of the hole injection. Changing the position of the long wavelength marker quantum well yields characteristic emission spectra which have been modelled with a multi scale carrier transport and luminescence simulator. The numerical modelling enables the extraction of opaque carrier transport characteristics in AlGaN such as the hole mobility in the highly doped barriers of the MQW.